A systematic literature review of green software development in collaborative knowledge management environment - Abdullah, Rusli; Abdullah, Salfarina; Din, Jamilah; Tee, Mcxin (Research India Publications, 2015)
Background: Main asset in software industry is knowledge of employees who work in software development. Knowledge is main asset to succeed in green sustainable development. There is no research about to implement techniques of Knowledge Management (KM) in order to help in managing knowledge of Green Software Development (GSD). This is the research gap.